Creatine kinase enzyme level correlates positively with serum creatinine and lean body mass, and is a prognostic factor for survival in amyotrophic lateral sclerosis. (31st March 2016) - Rafiq, M. K.; Lee, E.; Bradburn, M.; McDermott, C. J.; Shaw, P. J.
Abstract : Background and purpose: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative condition for which there is no single diagnostic test or biomarker. The level of the creatine kinase (CK) enzyme in serum may be mild to moderately elevated in some patients with ALS, the precise cause of which and its behaviour with disease progression is unknown. The aim of this study was to examine the usefulness of monitoring CK serially during the ALS disease trajectory and to determine whether CK levels mirror disease progression. Methods: This was a prospective observational cohort study, using the clinical database of the olesoxime (TRO19622) investigational medicinal product trial. Results: The baseline CK was raised in 52% of the trial participants with the mean CK ± SD being 257 ± 239 U/l. The mean CK was significantly higher in male participants than in female participants ( P < 0.001) and amongst participants with limb onset ALS compared to participants with bulbar onset ALS ( P < 0.001). There was no significant difference in the CK levels between upper limb and lower limb onset disease ( P = 0.746). The CK level co‐related positively with serum creatinine and estimated lean body mass but there was no relationship between CK and muscle scores and limb function. A higher CKlog was associated with significantly better survival, even when adjusted for prognostic co‐variants ( P = 0.013). Conclusions: The serum CK level seems to be an independent prognostic factor for survival in ALS. The cellular mechanism of CK enzyme suggests that it may be upregulated to provide energy in the face of metabolic stress in ALS.